Pengaruh Karakteristik Pasien Diabetes Melitus Tipe 2 Terhadap Kepatuhan Minum Obat di RSUD Jaraga Sasameh: The Impact of Characteristic Patient of Diabetes Mellitus Type 2 With Compliance Medication at RSUD Jaraga Sasameh - Widyasari, Meylinda; Herowati, Rina; Harsono, Samuel Budi (Universitas Kadiri, 2025)
Indonesia ranks fifth globally with 19.5 million diabetes cases [1]. The prevalence of diabetes mellitus (DM) in South Barito Regency reaches 1.05%, and 1.46% among individuals aged ≥15 years [2]. This study aims to identify patient characteristics that most influence adherence to type 2 DM treatment. Data were collected through validated questionnaires and analyzed using univariate, bivariate (chi-square test), and multivariate (multiple logistic regression) methods. The majority of respondents were aged 30–59 years, had low education levels, worked in the private sector, and 94.4% had comorbidities. Most were taking only one diabetes medication but received ≥4 other medications. The chi-square test results showed a significant relationship between the number and type of diabetes medications with adherence (p<0,05). Multivariate analysis revealed the number of medications received as the most influential factor (exp(B) = 2.519).